The Use of Visual Design in Teaching Speaking: Multimodality in the EFL Classroom - Seftika Seftika; Januarius Mujiyanto; Abdurrachman Faridi; Zulfa Sakhiyya (International Conference on Science, Education, and Technology, 2021)
This study investigates how the lecturer expresses meaning through visual design and explores the benefit of visual design as one of the multimodality elements for oral communication. This study involved one lecturer in one of the private universities in Indonesia majoring in English education as the participant. The data were taken from the lecturer's video-recorded teaching and interview. Then, the data were analyzed using thematic analysis. The finding shows that multimodality is necessary for teaching language. In addition, visual design is one of the multimodality elements that are very beneficial to the spoken communication of the EFL classroom. Using the visual design, the lecturer can deliver material for speaking class effectively; convey the message easily in synchronous and asynchronous learning (ASL) of speaking class; encourage students' confidence in speaking, and help students construct meaning-making in oral communication.